Usability and accessibility of institutional websites in demarcated wine regions: The cases of Vinhos Verdes and Douro - Costa, Eusébio (2021)
In this article we discuss the problem of usability and virtual accessibility and its importance in the municipalities websites in the Vinhos Verdes and Douro demarcated regions. In this context, the main objective of this article is focused on the analysis, especially quantitative, of the websites from two major demarcated regions: Vinhos Verdes (Sub-regions of Melgaço and Monção, Lima and Amarante) and Douro (Baixo and Cima Corgo) and the specific case of the municipalities websites, the Portal of the Vinho Verde and the Instituto dos Vinhos do Douro and Porto, in order to understand the degree of compliance with the requirements of the Web Content Accessibility Guidelines 2.0 of the World Wide Web Consortium (W3C). However, we support the analysis in the perspective of the wine tourist user.